2022
DOI: 10.3390/ijerph19063507
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Water, Sanitation, and Hygiene (WASH) and Spatial Distribution of Unimproved WASH in Nepal

Abstract: This study aims to estimate the prevalence and correlation of household levels of water, sanitation, and hygiene (WASH), including the identification of areas where WASH facilities are unimproved in Nepal. The study population was 11,040 household heads, using the data collected in the Nepal Demographic and Health Survey 2016. Logistic regression analysis was performed and crude odds ratios (OR) with 95% confidence intervals (CI) using a 0.05 significance level are presented. Getis–Ord Gi* statistics were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…[ 7 ] Complete lack of water and sanitation services globally was 12% and 21%, respectively, higher than those reported in this study (4.6% and 16.3%, respectively). [ 10 , 32 ] However, similar to the findings of this study, globally, about 16% of health-care facilities lacked hygiene services. [ 33 ]…”
Section: Discussionsupporting
confidence: 79%
“…[ 7 ] Complete lack of water and sanitation services globally was 12% and 21%, respectively, higher than those reported in this study (4.6% and 16.3%, respectively). [ 10 , 32 ] However, similar to the findings of this study, globally, about 16% of health-care facilities lacked hygiene services. [ 33 ]…”
Section: Discussionsupporting
confidence: 79%
“… Above variables were categorized according to the classification of previously published articles [ 1 , 23 ], PhD thesis [ 24 ] and DHS-7 guidelines [ 25 ]. …”
Section: Methodsmentioning
confidence: 99%
“…In 2021, approximately 96% of Nepalese households had improved water sources, 84% had access to a sanitary toilet, 81% had a fixed place for handwashing with soap, and 47% had soap and water available in a handwashing place [ 1 , 2 ]. There are few studies on individual household water, sanitation and hygiene (WASH) practices, and these do not specifically investigate the risk factors associated with mothers’ access to combined WASH in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of handwashing is normally called percentage of household mothers who washed their hands where denominator is the total number of households mothers included in the study. In 2023, Dhital et al conducted a cross sectional study using Nepal Demographic and Health Survey (NDHS) 2016 found the availability of soap and water was 47% [34]. Two municipalities Shankarapur and Tandi in Chitwan were 28% and 34%, respectively [35].…”
Section: Rates Of Household Handwashing With Soap By Mothers In Nepalmentioning
confidence: 99%
“…The key factors associated with handwashing with soap and water are education, wealth and ecology [34]. A cross-sectional study carried out among randomly selected mothers from 178 households in Makwanpur district in 2018 found maternal knowledge and the household wealth index affect handwashing with soap practices [36].…”
Section: Factors Associated With Maternal Handwashing In Nepalmentioning
confidence: 99%